PERAN MEDIA DALAM KOMUNIKASI POLITIK JELANG PEMILIHAN UMUM KEPALA DAERAH TAHUN 2017 DI KABUPATEN ACEH BARAT - Aminah Aminah (Universitas Teuku Umar, 2016)
Media in Political Communication ahead of the election widely used by the partner Regent and deputy Regent candidates to influence and seek sympathizers from the community, as happened in Aceh Barat District. Of the three candidates, namely pair H. T. Alaidin Syah and H. Kamaruddin, the couple H. Ramli MS and H. Banta Puteh Syam and the couple Fuad Hadi, SH., MH and drh. Muhammad Arif. This study describes the role of the media are executed by each pair of candidates Regent and deputy Regent of Aceh Barat ahead of the election simultaneously throughout Indonesia. This paper is based on a review of literature as well as by looking at the phenomenon of campaign located along Aceh Barat district. Based on the writer's observation, that each pair has the creativity respectively in the campaign (conveying political messages). Couple H. T. Alaidin Syah and H. Kamaruddin choose a political message by using the phrase